2022
DOI: 10.21203/rs.3.rs-1819108/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma level of ATPase inhibitory factor 1 (IF1) is associated with type 2 diabetes risk in humans: a prospective cohort study

Abstract: Background: Mitochondrial dysfunction is associated with the development of type 2 diabetes (T2D). It is thus of clinical relevance to identify plasma biomarkers of mitochondrial dysfunction associated with the risk of T2D.ATPase inhibitory factor 1 (IF1) endogenously inhibits mitochondrial ATP synthase activity. Here, we analyzed association of the plasma IF1 level with markers of glucose homeostasis and with the conversion to new-onset diabetes (NOD) in individuals with prediabetes.Methods: In the IT-DIAB pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…41,42 Recent studies have revealed that ecto-F 1 -ATPase serves as a high-affinity cell surface receptor for apoA-I in hepatocytes and endothelial cells and that it mediates key metabolic and vascular atheroprotective functions of HDL. 41,43 The clinical relevance of ecto-F 1 -ATPase in humans has been revealed by the finding that levels of circulating IF1 (ATPase inhibitory factor 1)-an endogenous inhibitor of the mitochondrial ATP synthaseare associated the risk for cardiovascular disease and T2D. [41][42][43] In cultured hepatocytes and endothelial cells, the introduction of an active form of recombinant IF1 induced a decrease in the production of extracellular ADP, leading to the attenuation of HDL effects.…”
Section: Editorial -Almentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Recent studies have revealed that ecto-F 1 -ATPase serves as a high-affinity cell surface receptor for apoA-I in hepatocytes and endothelial cells and that it mediates key metabolic and vascular atheroprotective functions of HDL. 41,43 The clinical relevance of ecto-F 1 -ATPase in humans has been revealed by the finding that levels of circulating IF1 (ATPase inhibitory factor 1)-an endogenous inhibitor of the mitochondrial ATP synthaseare associated the risk for cardiovascular disease and T2D. [41][42][43] In cultured hepatocytes and endothelial cells, the introduction of an active form of recombinant IF1 induced a decrease in the production of extracellular ADP, leading to the attenuation of HDL effects.…”
Section: Editorial -Almentioning
confidence: 99%
“…41,43 The clinical relevance of ecto-F 1 -ATPase in humans has been revealed by the finding that levels of circulating IF1 (ATPase inhibitory factor 1)-an endogenous inhibitor of the mitochondrial ATP synthaseare associated the risk for cardiovascular disease and T2D. [41][42][43] In cultured hepatocytes and endothelial cells, the introduction of an active form of recombinant IF1 induced a decrease in the production of extracellular ADP, leading to the attenuation of HDL effects. [44][45][46][47][48][49] With IF1 treatment in Ins-1E cells and isolated mouse islets, Manandhar et al observed an attenuation of apoA-I internalization and increased oxidative stress.…”
Section: Editorial -Almentioning
confidence: 99%